Effect of intraoperative active exploration of parathyroid glands to reduce the incidence of postoperative hypoparathyroidism, and risk factors of hypoparathyroidism after total thyroidectomy: a single-center study - Zhou, Bin; Cheng, Feng; Zhu, Xi; Zhu, Lei; Li, ZhouTing (Frontiers in Surgery, 2023)
The risk factors for hypoparathyroidism after thyroid surgery have not been fully identified. This study analyzes the risk factors of hypoparathyroidism before and after total thyroidectomy.We retrospectively collected the clinical data of 289 patients who underwent total thyroidectomy at the Thyroid Surgery Center of Lishui Central Hospital from June 2018 to June 2020.For the anatomy and protection of parathyroid glands during the operation, one group of patients used the parathyroid avoidance method, and the other group used the active exploration method.Various risk factors affecting parathyroid dysfunction were studied using logistic regression models.Results: A total of 289 patients were included in this study. The average age of patients was 47.21±11.78 years, including 57 males (19.7%) and 232 females (80.3%). There were 149 (51.6%) patients with transient hypoparathyroidism and 21 (7.3%) with permanent hypoparathyroidism. The main risk factors of hypoparathyroidism were parathyroid avoidance method (P=0.005), parathyroid autotransplantation (P=0.011), bilateral central neck lymph node dissection (CND) (P=0.001), lymphatic metastasis (P=0.039), and parathyroid in the specimen (P=0.029). The main risk factors associated with permanent hypoparathyroidism were bilateral CND (P=0.038), lymphatic metastasis (P=0.047), parathyroid hormone (PTH) <1.2 pg/ml within three days after surgery (P=0.006).Hypoparathyroidism is common but mostly transient after bilateral total thyroidectomy.Compared with parathyroid avoidance method, the active exploration method during operation may reduce the incidence of postoperative hypoparathyroidism. PTH <1.2 pg/ml within three days after surgery was predictive in patients with permanent hypoparathyroidism.